Question
upstudy study bank question image url

Find \( f+g, f-g, f g, \frac{f}{g} \). Determine the domain for each function. \( f(x)=\frac{9 x}{x-3}, g(x)=\frac{7}{x+7} \)

Ask by Romero Newton. in the United States
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the results for each operation between \( f(x) = \frac{9x}{x-3} \) and \( g(x) = \frac{7}{x+7} \), along with their domains: 1. **Sum (\( f + g \)):** \[ f + g = \frac{9x^2 + 70x - 21}{(x - 3)(x + 7)} \] *Domain:* \( x \neq 3 \) and \( x \neq -7 \) 2. **Difference (\( f - g \)):** \[ f - g = \frac{9x^2 + 56x + 21}{(x - 3)(x + 7)} \] *Domain:* \( x \neq 3 \) and \( x \neq -7 \) 3. **Product (\( f \cdot g \)):** \[ f \cdot g = \frac{63x}{(x - 3)(x + 7)} \] *Domain:* \( x \neq 3 \) and \( x \neq -7 \) 4. **Quotient (\( \frac{f}{g} \)):** \[ \frac{f}{g} = \frac{9x^2 + 63x}{7(x - 3)} \] *Domain:* \( x \neq 3 \) and \( x \neq -7 \) All functions are undefined at \( x = 3 \) and \( x = -7 \).

Solution

Let's compute each of the requested operations between the functions \( f(x) = \frac{9x}{x-3} \) and \( g(x) = \frac{7}{x+7} \). We'll also determine the domain for each resulting function. ### 1. Sum: \( f + g \) \[ f + g = \frac{9x}{x - 3} + \frac{7}{x + 7} \] To add these fractions, find a common denominator: \[ f + g = \frac{9x(x + 7) + 7(x - 3)}{(x - 3)(x + 7)} = \frac{9x^2 + 63x + 7x - 21}{(x - 3)(x + 7)} = \frac{9x^2 + 70x - 21}{(x - 3)(x + 7)} \] **Domain:** \( x \neq 3 \) and \( x \neq -7 \) --- ### 2. Difference: \( f - g \) \[ f - g = \frac{9x}{x - 3} - \frac{7}{x + 7} \] Find a common denominator to subtract the fractions: \[ f - g = \frac{9x(x + 7) - 7(x - 3)}{(x - 3)(x + 7)} = \frac{9x^2 + 63x - 7x + 21}{(x - 3)(x + 7)} = \frac{9x^2 + 56x + 21}{(x - 3)(x + 7)} \] **Domain:** \( x \neq 3 \) and \( x \neq -7 \) --- ### 3. Product: \( f \cdot g \) \[ f \cdot g = \frac{9x}{x - 3} \times \frac{7}{x + 7} = \frac{63x}{(x - 3)(x + 7)} \] **Domain:** \( x \neq 3 \) and \( x \neq -7 \) --- ### 4. Quotient: \( \frac{f}{g} \) \[ \frac{f}{g} = \frac{\frac{9x}{x - 3}}{\frac{7}{x + 7}} = \frac{9x}{x - 3} \times \frac{x + 7}{7} = \frac{9x(x + 7)}{7(x - 3)} = \frac{9x^2 + 63x}{7(x - 3)} \] **Domain:** \( x \neq 3 \) and \( x \neq -7 \) --- ### Summary of Results 1. **Sum:** \[ f + g = \frac{9x^2 + 70x - 21}{(x - 3)(x + 7)}, \quad \text{Domain: } x \neq 3, -7 \] 2. **Difference:** \[ f - g = \frac{9x^2 + 56x + 21}{(x - 3)(x + 7)}, \quad \text{Domain: } x \neq 3, -7 \] 3. **Product:** \[ f \cdot g = \frac{63x}{(x - 3)(x + 7)}, \quad \text{Domain: } x \neq 3, -7 \] 4. **Quotient:** \[ \frac{f}{g} = \frac{9x^2 + 63x}{7(x - 3)}, \quad \text{Domain: } x \neq 3, -7 \] All resulting functions are defined for all real numbers except \( x = 3 \) and \( x = -7 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To find \( f + g \), \( f - g \), \( fg \), and \( \frac{f}{g} \), we start with the given functions: \[ f(x) = \frac{9x}{x-3}, \quad g(x) = \frac{7}{x+7} \] 1. **Sum \( f + g \)**: \[ f + g = \frac{9x}{x-3} + \frac{7}{x+7} \] To add these, we need a common denominator, which is \((x-3)(x+7)\): \[ f + g = \frac{9x(x+7) + 7(x-3)}{(x-3)(x+7)} = \frac{9x^2 + 63x + 7x - 21}{(x-3)(x+7)} = \frac{9x^2 + 70x - 21}{(x-3)(x+7)} \] The domain excludes \( x = 3 \) and \( x = -7 \). 2. **Difference \( f - g \)**: \[ f - g = \frac{9x}{x-3} - \frac{7}{x+7} \] Using the same common denominator: \[ f - g = \frac{9x(x+7) - 7(x-3)}{(x-3)(x+7)} = \frac{9x^2 + 63x - 7x + 21}{(x-3)(x+7)} = \frac{9x^2 + 56x + 21}{(x-3)(x+7)} \] The domain is the same, excluding \( x = 3 \) and \( x = -7 \). 3. **Product \( fg \)**: \[ fg = \frac{9x}{x-3} \cdot \frac{7}{x+7} = \frac{63x}{(x-3)(x+7)} \] The domain excludes \( x = 3 \) and \( x = -7 \). 4. **Quotient \( \frac{f}{g} \)**: \[ \frac{f}{g} = \frac{\frac{9x}{x-3}}{\frac{7}{x+7}} = \frac{9x(x+7)}{7(x-3)} \] The domain excludes \( x = 3 \) and \( x = -7 \), but we must also note \( g(x) \neq 0 \) which is \( x \neq -7 \). In summary: - \( f + g = \frac{9x^2 + 70x - 21}{(x-3)(x+7)} \) - \( f - g = \frac{9x^2 + 56x + 21}{(x-3)(x+7)} \) - \( fg = \frac{63x}{(x-3)(x+7)} \) - \( \frac{f}{g} = \frac{9x(x+7)}{7(x-3)} \) The common domain for all functions is \( x \in \mathbb{R} \setminus \{3, -7\} \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy